2023
DOI: 10.36408/mhjcm.v10i1.847
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Urinary Diversion in Patients with Cervical Cancer at Kariadi General Hospital

Abstract: BACKGROUND: Obstructive uropathy and hydronephrosis are common complications of cervical cancer. In order to provide an alternative route due to ureteral obstruction, urinary diversion was performed. Urinary diversion procedures are a therapeutic option for obstructive uropathy but their effectiveness is remain unclear. There is limited data that support urinary diversion as a treatment of ureteral obstruction to improve overall survival and progression-free survival. AIM:  To determine the effectiveness of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies also reported that the 1-year survival of patients who underwent deobstruction was higher J Indon Med Assoc, Volum: 74, Nomor: 2, April -Mei 2024 than those who did not. 13 Based on the type of deobstruction, DJ stent, PCN, and UCS insertion showed similar survival rate. These results are similar to the results of a previous study which found that both PCN insertions and ureteral stents offered similar survival rates in patients with advanced cervical cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies also reported that the 1-year survival of patients who underwent deobstruction was higher J Indon Med Assoc, Volum: 74, Nomor: 2, April -Mei 2024 than those who did not. 13 Based on the type of deobstruction, DJ stent, PCN, and UCS insertion showed similar survival rate. These results are similar to the results of a previous study which found that both PCN insertions and ureteral stents offered similar survival rates in patients with advanced cervical cancer.…”
Section: Discussionmentioning
confidence: 91%